Programmable negative differential resistance effects based on self-assembled Au@PPy core-shell nanoparticle arrays - Zheng, Jianzhong (2020)
The negative differential resistance (NDR) effect observed in conducting polymer/Au nanoparticle composite devices is not yet fully clarified due to the random and disordered incorporation of Au nanoparticles into conducting polymers. It remains a formidable challenge to achieve the sequential arrangement of various components in an optimal manner during the fabrication of Au nanoparticle/conducting polymer composite devices. Here, a novel strategy for fabricating Au nanoparticle/conducting polymer composite devices based on self-assembled Au@PPy core-shell nanoparticle arrays is demonstrated. The interval between the two Au nanoparticles can be precisely programmed by modulating the thickness of the shell and the size of the core. Programmable NDR is achieved by regulating the spacer between two Au nanoparticles. In addition, the Au/conducting polymer composite device exhibits a reproducible memory effect with read-write-erase characteristics. The sequentially controllable assembly of Au@PPy core-shell nanoparticle arrays between two microelectrodes will simplify nanodevice fabrication and will provide a profound impact on the development of new approaches for Au/conducting polymer composite devices.